2013
DOI: 10.1371/journal.pone.0059583
|View full text |Cite
|
Sign up to set email alerts
|

Pre-S Deletion and Complex Mutations of Hepatitis B Virus Related to Young Age Hepatocellular Carcinoma in Qidong, China

Abstract: Background/AimTo investigate the roles of biomedical factors, hepatitis B virus (HBV) DNA levels, genotypes, and specific viral mutation patterns on the progression of hepatocellular carcinoma (HCC) patients below 40 years of age in Qidong, China.MethodsWe conducted a case-control study within a cohort of 2387 male HBV carriers who were recruited from August, 1996. The HBV DNA sequence was determined in 49 HCC and 90 chronic hepatitis (CH) patients below 40 years of age. Mutation exchanges during follow-up in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…To our best knowledge, up to now, there are only limited longitudinal studies of pre-S mutations in relation to the development of HCC. Qu et al [ 25 ] showed that complex HBV mutations (pre-S deletions, T1762/A1764, and T1766 and/or A1768 mutants) were gradually combined during the development of HCC. Our previous study [ 12 ] also reported the emergence of de novo pre-S deletions before the development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, up to now, there are only limited longitudinal studies of pre-S mutations in relation to the development of HCC. Qu et al [ 25 ] showed that complex HBV mutations (pre-S deletions, T1762/A1764, and T1766 and/or A1768 mutants) were gradually combined during the development of HCC. Our previous study [ 12 ] also reported the emergence of de novo pre-S deletions before the development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…THE ANALYSIS USED data and stored samples from a prospective cohort in Qidong, Jiangsu Province, China . From 1 August to 30 September 1996, a total of 18 000 males aged 20–65 years, who were living in 17 townships of Qidong, were invited to participate in this HCC screening study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the classical A1762T/G1764A double mutation within the basal core promoter (nt 1742–1849 from EcoR I site) and the G1896A mutation in the precore (PC) (nt 1814–1900 from EcoR I site) region are often reported to be associated with advanced liver diseases including liver cirrhosis and HCC in HBV mono-infection [8], [9], [10], [11]. Similarly, the presence of Pre-S1/S2 deletion have also been reported to be associated with progressive liver disease [12] and increased risk for HCC [13] in HBV mono-infection. Moreover, the frequency of PreS2 deletion was previously found to be higher among the HIV/HBV co-infected population [14].…”
Section: Introductionmentioning
confidence: 99%